Demographic Differences in the Challenges and Adaptations of Filipino Senior High School Teachers - Asi, Roel; Macarandang, Mercedes (JPAIR Institutional Research, 2020)
The study focused on determining the challenges met by the teachers concerning as they migrated to Senior High School and their adaptations to meet the identified challenges. The descriptive survey method was a questionnaire.  Respondents of the study were select fifty private and fifty public senior high school teachers in Lipa City.  The data gathered were analyzed using frequency counts, weighted mean, standard deviation, ranking, t-test, and analysis of variance (ANOVA).  The study found out that senior high school teachers met challenges in preparing paper works, assessing students' performance, understanding the new curriculum, asserting their authority among students, coping with misbehaving students, diagnostic assessment, dealing with unfriendly and ill-mannered colleagues, and meeting high expectations from sources. Discussions with colleagues and keeping abreast of new technologies are their ways of adaptation. The respondents from public and private schools differed significantly in their mechanisms.
Keywords: Education; Transitional challenges; adaptations; senior high school; teachers